Dual Role of Toll-like Receptors in Human and Experimental Asthma Models - Zakeri, Amin; Russo, Momtchilo (Frontiers in Immunology, 2018)
Asthma is a chronic airway inflammatory disease that is influenced by the interplay between genetic factors and exposures to environmental allergens, microbes or microbial products where Toll-like receptors (TLRs) play a pivotal role. TLRs recognize a wide range of microbial or endogenous molecules as well as airborne environmental allergens and act as adjuvants that influence positively or negatively allergic sensitization. TLRs are qualitatively and differentially expressed on hematopoietic and non-hematopoietic stromal or structural airway cells that when activated by TLRs agonists exert an immune-modulatory role in asthma development. Therefore, understanding mechanisms and pathways by which TLRs orchestrate asthma outcomes may offer new strategies to control the disease. Here, we aim to review and critically discuss the role of TLRs in human asthma and murine models of allergic airway inflammation, highlighting the complexity of TLRs function in development, exacerbation or control of airway allergic inflammation.